Development of Adaptive Bandwidth Allocation Model Using PCQ for Network Performance Optimization - Salkin Lutfi; Syarifuddin Kapita; Hairil Kurniadi Sirajuddin; Yasir Muin (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The number of clients has an impact on network performance, and while more bandwidth capacity can sometimes result in better network services, it is not always a given. Clients acquire the appropriate bandwidth, which is managed at the network layer by software, to control the flow and number of packets in the network. The practice of managing bandwidth includes measuring and controlling communications (traffic and packets) through network channels. This is done to prevent overburdening or overloading networks, which will lead to network congestion and poor performance. The goal of this study is to improve the internet network through bad-width allocation using the PCQ approach. When it comes to sharing bandwidth with active users and large users, the results of the suggested strategy are excellent.